The Role of Zinc Supplementation in The Lung Tissue Damage of Tuberculosis Rats - Sukma Sukma Sahadewa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2020)
Infection by Mycobacterium tuberculosis (Mtb) is a chronic contagious disease with a high mortality rate in various parts of the world, especially in developing countries with high poverty rates. The objective of the present study was to examine the effects of zinc supplementation on the lung tissue damage of the male tuberculosis rats. This study was conducted based on true experimental design, using a post-test control group design. Peribronchiolitis was found to have a higher rank in (K0, K1, K2) groups compared to the Mtb group treated with the addition of Zinc supplements (P1, P2, P3). Zinc supplementation in this study shows that there is a reduction in lung organ damage and having a positive impact on increasing the perivasculitis and granuloma. Zinc supplementation by its optimal dose of 50 mg/kg.bb/day given as additional nutrition in Mtb rats.